Catalisadores heterogêneos suportados em materiais de carbono porosos partindo de rejeitos de uma rocha ornamental carbonática : preparação, caracterização e aplicação para obtenção de biodiesel - Aleixo, Fábio da Costa (2025)
The processing of carbonate rocks generates substantial amounts of waste, which are frequently mismanaged—either discarded into the environment or irregularly deposited in landfills—posing significant environmental concerns. This study explores the synthesis of heterogeneous catalysts supported on a carbonaceous matrix, using carbonate ornamental stone tailings (OST) as a low-cost source of calcium and magnesium oxides. Various chemicals routes were initially evaluated, with all materials subjected to thermal treatment at 800 °C for 3 hours under an inert atmosphere. Among them, the wet impregnation method involved mixing OST and coconut shell-activated carbon (CSAC) powders with a NaOH solution under constant stirring. In a subsequent step, the synthesis parameters for this method were optimized using a full factorial experimental design. The catalytic performance of the resulting materials was assessed in the transesterification of soybean oil with methanol for biodiesel production. Conversion efficiency was monitored and quantified by proton nuclear magnetic resonance spectroscopy in solution. Among the tested synthesis routes, wet impregnation yielded the highest conversion rates. In the optimization study, a maximum conversion of 85% was achieved using an OST/CSCA mass ratio of 50:20, followed by thermal treatment at 800 °C for 1 hour. Further optimization of the reaction conditions, performed via a central composite design, led to a maximum biodiesel yield of 91% under the following conditions: 5 wt% catalyst loading (relative to oil mass), 3 hours of reaction time, and a temperature of 60 °C. The catalysts demonstrated excellent activity, attributed to the formation of CaO, MgO, Na₂CO₃, and Na₂CO₃·CaCO₃ phases, as confirmed by X-ray diffraction, depending on the thermal treatment parameters. Analysis of the Ca and Mg content in the biodiesel revealed significantly reduced metal leaching when CACO was used as the support, with concentrations remaining below or only slightly above the 5.0 mg/kg threshold established by the European standard EN 14214. These findings confirm the feasibility of employing OST and coconut shells as sustainable feedstocks for the development of efficient, carbon-supported heterogeneous catalysts. The wet impregnation route emerged as the most effective strategy for depositing calcium and magnesium oxides onto the CSCA matrix, offering both economic and environmental advantages due to its reliance on waste-derived materials and minimal generation of secondary residues